The Impact of Implementing a Community-Based Training Model with a Coaching and Contextual Approach in the Era of Merdeka Belajar - Imron, Imron; Pramono, Suwito Eko; Rusilowati, Ani; Sulhadi, Sulhadi; Maulana, Vicky Ainul Hayya (Proceedings of International Conference on Science, Education, and Technology, 2024)
Teachers' competencies are continuously improved to help more students acquire skills. The 2023 Education Report Card results are in line with the 2018 and 2022 PISA results. The government's breakthrough is the Merdeka Belajar program, with the hope of increasing superior and competitive human resources towards Golden Indonesia 2045. The problem that occurs today is that the various trainings that have been carried out have not been seen to have an impact on learning leadership. This study aims at the impact of training implementation, especially teacher competency, on learning leadership. The methodology used mixed methods research. Findings in the study: the average increase in grades was 27.02; students felt happy, interested and not afraid to learn math again when taught by teachers who participated in the training; the principal strongly supports the training activities carried out by the community and hopes that the Government through the Education Office will facilitate it for other teachers or schools; and teachers who participated in the training felt comfortable teaching math and were happy when coaching was carried out; The conclusion of this study is that the implementation of this training model has a significant impact on students, teachers, and schools, especially in learning leadership.